Regulation, Market Structure and Performance in Air Passenger Transportation - Gönenç, Rauf (OECD Publishing, 2000)
The paper uses a data base on regulation, market structure and performance in the air passenger transportation industry, to analyse the links among liberalisation, private ownership, competition, efficiency and airfares at national and route levels. Covering the 1996-97 travel season, 21 aggregate indicators have been developed for 27 OECD countries, and 23 micro indicators for 102 air routes connecting 14 major international airports. These data, summarised by means of factor analysis show that i) regulations affecting the air industry vary heavily across countries and routes; ii) in most markets, air services are still provided by a few carriers, generally dominated by an incumbent flag-carrier or by an airline alliance between incumbents; iii) only in a few cases new entrant airlines play a significant role; iv) in a large number of airports, a single airline controls more than half of the available slots; v) as a result, few international routes are truly open to ...
Keywords: Economics